أحكام رهن العلامة التجارية: دراسة مقارنة - إبراهيم، مجيد أحمد; نجم، عمر على (جامعة كركوك - كلية القانون والعلوم السياسية, 2022)
إن العلامة التجارية أداة لتمييز بضائع تاجر عن تاجر أخر، والعلامة التجارية بعدها مال منقول معنوي، ترد عليها العديد من التصرفات، منها ما يكون ناقلة للملكية كالبيع، ومنها ما يكون غير ناقل للملكية كالرهن، وبقدر تعلق الآمر برهن العلامة التجارية، فأن رهن العلامة التجارية عقد كسائر العقود يخضع لما يخضع له أي عقد من حيث توافر الأركان العامة للعقد من رضا ومحل وسبب، كذلك يعد تصرف شكلي من حيث التسجيل والإشهار والإعلان، وبالوقت نفسه تترتب عليه العديد من الآثار، وقد اكتفينا بالالتزامات المترتبة على عاتق الراهن على اعتبار أن العلامة التجارية لن يسلمها إلى الدائن المرتهن، كونه بحاجة إلى السيولة النقدية لديمومة عمله التجاري، لذلك انعقد عقد الرهن لمصلحته. The trademark is an instrument to distinguish merchandise merchandise from another merchant, and the trademark after it is immovable money, to which many actions are returned, including what is a transfer of ownership such as sale, and some of which are not transferable to ownership like a mortgage, and as far as the matter relates to the mortgage of the trademark, then the mortgage of the trademark A contract, like all contracts, is subject to the satisfaction, place and reason for any contract subject to the availability of the general elements of the contract, as well as a formality in terms of registration, publicity, and advertising, and at the same time it has many effects, and we have satisfied ourselves with the obligations of the current person, given that the trademark will not Hand it over to the Organism mortgagee, being in need of cash for the sustainability of its business, so the mortgage contract was held for him.
Keywords: القانون التجاري -- المحلات التجارية -- الرهن التأميني -- العراق